Late complications of radiotherapy for nasopharyngeal carcinoma - Yupa Sumitsawan (2018)
Objective: To evaluate and assemble late complications of radiotherapy in cases of nasopharyngeal cancer. Methods: From October 2003 to January 2005, a prospective cohort study was done in a tertiary center, Chiang Mai University Hospital. Two hundred patients were evaluated for late complication according to the RTOG/EORTC late radiation morbidity scoring criteria. Results: Of 200 patients, 131 were male (65.5%) and 69 female (34.5%). The mean age was 49.7 ± 13.5 years (11-78). The mean pre- and post-treatment body mass indexes (BMI) were 22.5 ± 4 (15-35.6), and 19.8 ± 3.2 (12.9-34.5; P < 0.05). Mean post-radiation period was 3.6 ± 3.4 years (0.3-18.6 years). The radiation dosage ranged from 60 to 76 Gy (mean 69 Gy). Most of the patients (92%) had undifferentiated (50.5%) and poorly differentiated (41.5%) squamous cell carcinoma. Eighty-eight percent of the patients were in Stage III and IV. Chemotherapy was given to 145 patients (72.5%). The mean post-radiation period in the added chemotherapy group was lower than the group treated with radiation alone (2.9 ± 2.7 years vs. 5.4 ± 4.4 years, P < .05). The most common complication was dryness of mouth (97.5%); followed by hearing impairment (inner ear 82.5%). Added chemotherapy increased the complication severity significantly for the skin (P < 0.05). The mean number of complications was 6.3 ± 2.2 (range from 1 to 12). Conclusion: In this study, every patient had a more or less adverse reaction to radiation. Doctors need to be aware of these complications in order to prevent serious ones and to improve the patients' quality of life in the long term. © 2008 Elsevier Ireland Ltd. All rights reserved.